The cold way for glutathione biosynthesis in the psychrophile Pseudoalteromonas haloplanktis. Redundancy and reaction rates. Issue 74 (25th July 2016) - Albino, Antonella; De Angelis, Amalia; Rullo, Rosario; Maranta, Chiara; Capasso, Alessandra; Ruocco, Maria Rosaria; Sica, Filomena; De Vendittis, Emmanuele
Abstract : In the psychrophile P. haloplanktis GSH is formed in two consecutive steps coupled to ATP hydrolysis. Differently from other sources, two redundant γ-glutamyl cysteine ligases catalyse first step; overall GSH biosynthesis is rate-limited by second step. Abstract : This work describes major features and specificities of glutathione (GSH) biosynthesis in the cold-adapted Pseudoalteromonas haloplanktis . Two steps of ATP hydrolysis, catalysed by γ-glutamyl-cysteine ligase ( Ph GshA) and glutathione synthetase ( Ph GshB), drive GSH formation; however, differently from other sources, this psychrophile contains two redundant Ph GshAs. The biochemical properties of recombinant r Ph GshB and r Ph GshA II were previously reported; here we report the characterization of r Ph GshA I, together with a structural comparison with r Ph GshA II. The availability of the three enzymes involved in GSH biosynthesis allowed the reconstitution of two systems producing this thiol in P. haloplanktis . Both systems were active, although with different reaction rates; in particular, r Ph GshB worked more efficiently with r Ph GshA I compared to r Ph GshA II, also because of the different expression of the corresponding genes. However, the lower K M of r Ph GshA II for cysteine compared to r Ph GshA I could permit an effective GSH production even under conditions of low cysteine content. Coupling of the kinetics of GSH production with that of ATP hydrolysis was realised for the first time and proved the rigorous stoichiometry of GSH biosynthesis, resulting in two moles of ATP hydrolysed per one mole of GSH formed. Furthermore, after dissecting the reaction rates for GSH biosynthesis, we demonstrated that synthesis of this thiol was rate-limited by the step catalysed by r Ph GshB, at least in the cold-adapted source. Therefore, the GshA rate-limited step postulated in other sources could be revised or restricted to conditions of limiting substrate amounts.